Incidence of Hypothyroidism (High Tsh) In Newborns Delivered Through Lscs In A Government Medical College Sindhudurg - Dr. Nagargoje Ramchandra; Dr. Swayamprabha Ulhas Pawar; Dr. Dhananjay Ankush Bhosale, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Congenital Hypothyroidism is most common cause of preventable mental retardation in neonates. The incidence of congenital hypothyroidism is approximately 1:2000 to 1:4000 newborns worldwide. Incidence in India is 1: 2500 – 1:2800 live births. Clinical manifestations of hypothyroidism in newborns are subtle, or not present at birth. Early diagnosis and treatment are of paramount importance to prevent mental retardation. Aim and Objectives: 1. Incidence of Hypothyroidism (High TSH) in Newborns delivered through LSCS in a Government Medical College Sindhudurg.2.Study the risk factors of congenital hypothyroidism.3.Study clinical profile of Hypothyroidism in newborns Material and Methods: Study design: Prospective study, Study settings: Pediatric department of GMC Sindhudurg. Study population: All newborns with hypothyroidism among LSCS cases in a GMC Sindhudurg during study period such cases were included in the study. Study period: June 2023 To June 2025 Result: majority of cases were Females 43 (58.10%) cases and 30 (41.89%) cases were males. most of the newborn presented with 2 to 2.5 kg birth weight 49 (66.21%) cases. most of the cases Apgar score at 1 minute was >5 56 cases, most of the newborn status was AGA 67 (90.54%) most common maternal complication was anemia 23 (31.08%), Hypothyroidism in 10 (13.51%) cases, all cases presented with congenital hypothyroidism 74 followed by hypoglycemia 6, birth asphyxia 5 cases, respiratory distress 5, neonatal seizures 4,hypocalcemia 2 cases and birth trauma in 1 case. Incidence of Hypothyroidism (High TSH) in Newborns delivered through LSCS was 8.70%. There is statistically significant association between clinical outcomes with Neonatal status. Conclusion: majority of cases were Females, Incidence of Hypothyroidism (High TSH) in Newborns delivered through LSCS was 8.70%. There is statistically significant association between clinical outcomes with Neonatal status.